Sosialisasi Pencegahan Stunting Sejak Dini pada Ibu Hamil dan Ibu Balita - Sartika Maulida Putri; Julia Anita; Anggawinata; Cut Husnul Khatimah; Fita Nelyza (Jurnal Mitra Pengabdian Farmasi, 2022)
Community service activities regarding the socialization of stunting prevention to pregnant women and toddlers from an early age in Gampong Geuceu Komplek Banda Raya District Banda Aceh City aims to improve health education to the community, especially pregnant women and mothers with toddlers related to stunting, how to prevent stunting, child characteristics who experience stunting and how to process food so that it has balanced nutrition but is cheap and easy to obtain by the community, this community service also motivates the community to be more intense and focus on the health of their families and environment, here also explains how to cope if children experience stunting, so that they can immediately and children do not experience stunting until adult, the impact of stunting is not only related to height but also related to future health and intelligence. Hopefully this socialization can reduce the number of stunting in Aceh in particular.